Analisis Algoritma Klasifikasi C 4.5 Untuk Memprediksi Keberhasilan Immunotherapy Pada Penyakit Kutil - Ady Hermawan; Ardi Ramadhan Sukma; Riqardi Halfis (JURNAL TEKNIK KOMPUTER, 2019)
Maintaining skin health is one thing that is also needed. Not only health from inside, health from the outside must also be considered. There are so many skin problems that arise in the human body. Wart disease is characterized by small bumps on the surface of the skin which are generally caused by the Human Papiloma Virus (HPV) virus. One technique for treating wart disease is immunotherapy, this method is a treatment by increasing the immune system to deal with wart disease. Clinical predictions are growing very rapidly by adopting computer science and information technology in managing health and drug data, this clinical prediction can be produced from processing using data mining methods. Data mining is a popular method used to explore patterns or knowledge from large data stacks. C 4.5 algorithm which is one of the decision tree induction algorithms is also a method of data mining algorithms used to classify. This study aims to predict the success rate of immunotherapy treatment methods on wart disease with algorithm C 4.5 using RapidMiner. From the study it was known that the accuracy rate for processing immunotherapy data on wart disease to predict its success using the C 4.5 algorithm of 74.07%.